The Relationship of Exposure to Cigarette Smoke in the Room to the Event of Ari on Children in Asembagus Puskesmas Situbondo District - Nanda, Febrika Devi; Sasongko, Hendrik Probo; Murdani, Agus Putra (Journal for Quality in Public Health, 2021)
Acute respiratory tract infection is the process of entry of a microorganism into the respiratory tract organs which can cause an antibody antigen response and lasts up to 14 days. According to the World Health Organization in 2007, ARI is one of the causes of death in children under five in developing countries. One of the risk factors for the occurrence of ARI is due to exposure to cigarette smoke. This study aims to determine the relationship between exposure to cigarette smoke in the room and the incidence of ARI in toddlers at Asembagus Public Health Center, Situbondo Regency. The type of research used in this study is in the form of an analytical study using a cross sectional approach. The number of population contained in this study were 34 patients under five. Then, after the sampling technique was carried out in the inclusion criteria and exclusion criteria, a total sample of 30 respondents was obtained which were analyzed using the Linear Regression statistical test with the help of SPSS software for windows version 17. The results showed that the distribution of high and low exposure to cigarette smoke in the room in the respondents found that most of the respondents (73.33%) had a high level of exposure to cigarette smoke. Meanwhile, the distribution of ARI incidence among toddlers, most (63.33%) was at the moderate ARI incidence rate. From the results of the calculation of the linear regression statistical test, it can be concluded that there is a significant positive relationship of 0.403 between exposure to cigarette smoke in the room to the incidence of ARI in toddlers at Asembagus Public Health Center in 2020. The level of exposure to cigarette smoke exposure to the incidence of ARI depends on the concentration of cigarette smoke gathered in a closed room according to the number of smokers, the type of cigarette smoked and the characteristics of the room conditions, for example, the size of ventilation, air temperature and humidity, and the habits of toddlers who are in a non-smoking area.